2021
DOI: 10.1111/jora.12705
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Are More Likely to Help Others on Days They Take Risks and Crave Social Connections

Abstract: This study examined how adolescents' risk-taking behaviors were related to their prosocial behaviors on a daily level and how this association differed depending on adolescents' daily and average levels of sensation seeking and social craving. Adolescents (N = 212; M age = 15 years) completed daily diaries for 14 days. Adolescents were more likely to engage in prosocial behavior on days when they also took risks, but only when they also felt high levels of social craving. The daily link between risk-taking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For instance, prosocial and rebellious behaviors are positively correlated across adolescence (Blankenstein et al, 2020). Moreover, on days when adolescents tend to be risky, they are also more likely to engage in prosocial behaviors if they also crave social interactions (Armstrong-Carter et al, 2021). Interestingly, risk-taking and prosocial behaviors converge across adolescence, such that they are anticorrelated early in adolescence but become positively correlated by mid-adolescence (Armstrong-Carter et al, 2022).…”
Section: Adolescents Are Not Overly Selfish But Are Remarkably Other-...mentioning
confidence: 99%
“…For instance, prosocial and rebellious behaviors are positively correlated across adolescence (Blankenstein et al, 2020). Moreover, on days when adolescents tend to be risky, they are also more likely to engage in prosocial behaviors if they also crave social interactions (Armstrong-Carter et al, 2021). Interestingly, risk-taking and prosocial behaviors converge across adolescence, such that they are anticorrelated early in adolescence but become positively correlated by mid-adolescence (Armstrong-Carter et al, 2022).…”
Section: Adolescents Are Not Overly Selfish But Are Remarkably Other-...mentioning
confidence: 99%
“…This personality trait is associated with risky driving (Lemarie, Bellavance, & Chebati, 2019), engaging in extreme sports (Ruedl et al 2012;Kopp et al, 2016;Breivik, Sand, & Sookermany, 2017;Permadani & Jannah, 2022), substance abuse (Evans-Polce et al, 2018), and criminal behavior (Armstong et al, 2020). There are also studies showing that the degree of Sensation seeking varies from individual to individual and that Sensation-seeking tendency is linked to both negative (Rosenbloom, 2003;Robbins & Bryan, 2004;Fillmore, Ostling, Martin, & Kelly, 2009;Ortin, Lake, Kleinman, & Gould, 2012) and positive (Ravert et al, 2013;Armstrong et al, 2021) risk-taking behaviors. Zuckerman (2007) characteristically considered Sensation-seeking behavior in four different dimensions and expressed these dimensions as Sensation and adventure seeking, experience seeking, reduced control over one's behavior, and susceptibility to boredom.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by facilitating connectedness is also an effective way to achieve social benefits ( Pavey et al, 2011 ; McLoughlin and Hermens, 2018 ). Armstrong-Carter et al (2021) suggested that strong prosocial tendencies arise when adolescents feel highly motivated to connect with others. Van Ryzin et al (2020) also verified that more positive peer relationships contribute to higher levels of PB through a study of the relationship between cooperative learning and PB.…”
Section: Introductionmentioning
confidence: 99%